GTPase Regulator Associated with Focal Adhesion Kinase 1 (GRAF1) Immunoglobulin‐Associated Ataxia and Neuropathy - Pittock, Sean J. (Mov Disord Clin Pract, 2020)
BACKGROUND: To date, 10 patients with GTPase Regulator Associated with Focal Adhesion Kinase 1/Rho GTPase Activating Protein 26‐Immunoglobulin (GRAF1/ARHGAP26‐IgG) associated neurological disorders have been described, most with ataxia. OBJECTIVE: To report the clinical, oncological, and radiological associations of GRAF1 autoantibodies. METHODS: We identified 17 patients whose serum and/or cerebrospinal fluid IgG was confirmed to target GRAF1/ARHGAP26‐IgG by both tissue‐based immunofluorescence and transfected cell‐based assay. Clinical information was available on 14 patients. RESULTS: The median age at neurological symptom onset was 51 years, and 8 (47%) were men. The predominant clinical features were subacute progressive cerebellar ataxia (13) or peripheral neuropathy (2). Magnetic resonance imaging brain (7 available) showed cerebellar atrophy (4, 1 also cerebrum and brainstem atrophy). Of 7 cerebrospinal fluids available for testing, 5 showed pleocytosis with oligoclonal bands in 3. Squamous cell carcinoma was observed in 3 patients (head and neck [2], lung [1]). CONCLUSION: GTPase Regulator Associated with Focal Adhesion Kinase 1 autoimmunity manifests commonly with subacute ataxia and cerebellar degeneration with a potential association with squamous cell carcinoma. Peripheral neuropathy may also be encountered. Cases in this series responded poorly to immunotherapy.